2008
DOI: 10.3171/jns/2008/108/4/0791
|View full text |Cite
|
Sign up to set email alerts
|

Effective suppression of hippocampal seizures in rats by direct hippocampal cooling with a Peltier chip

Abstract: Selective hippocampal cooling effectively suppresses the KA-induced hippocampal EDs. Direct hippocampal cooling with a permanently implantable system is potentially useful as a minimally invasive therapy for temporal lobe epilepsy and therefore could be an alternative to the temporal lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…27 This group then showed that they could cool deep into the rat hippocampus by attaching an insulated needle to a Peltier device held away from the brain surface. 28 A limited set of unpublished observations on a single monkey have verified that our thermoelectric device is capable of inhibiting function in the primate neocortex. When our thermoelectric device was placed in direct contact with the pia on the surface of the hand region of the pre-central gyrus, there was a consistent, reversible impairment in skilled finger movements associated with a reduction in surface temperature.…”
Section: ™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™mentioning
confidence: 77%
“…27 This group then showed that they could cool deep into the rat hippocampus by attaching an insulated needle to a Peltier device held away from the brain surface. 28 A limited set of unpublished observations on a single monkey have verified that our thermoelectric device is capable of inhibiting function in the primate neocortex. When our thermoelectric device was placed in direct contact with the pia on the surface of the hand region of the pre-central gyrus, there was a consistent, reversible impairment in skilled finger movements associated with a reduction in surface temperature.…”
Section: ™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™mentioning
confidence: 77%
“…It is necessary to differentiate this prediction of a retrograde gradient from the shown anterograde preservation of working memory capacity following MTL damage encompassing the hippocampus (Jeneson et al, 2010; Jeneson and Squire, 2012). To the authors knowledge, a retrograde preservation of active working memory traces has not been shown before and constitutes a testable prediction, given neurophysiological deactivation of hippocampal function on the timescale of working memory, such as focal cooling may allow (Tanaka et al, 2008). Experimental lesion studies (Squire and Cohen, 1979; Winocur, 1990; Zola-Morgan and Squire, 1990; Kim and Fanselow, 1992) simply cannot account for the fleeting storage of new percepts in short-term memory.…”
Section: Discussionmentioning
confidence: 96%
“…21) Encouraged by these studies, our group has begun to examine the practicality of focal brain cooling as a therapy for patients with intractable epilepsy. 14,27) …”
Section: History Of Brain Cooling As a Therapy For Epilepsymentioning
confidence: 99%
“…27) The cooling needle, which was attached to the Peltier chip, a thermocouple, and a needle electrode for EEG recording were inserted into the right hippocampus. KA was injected into the left hippocampus to provoke EDs.…”
Section: Hippocampal Seizure Modelmentioning
confidence: 99%
See 1 more Smart Citation